2021
DOI: 10.3390/pathogens11010045
|View full text |Cite
|
Sign up to set email alerts
|

Omicron SARS-CoV-2 Variant Spike Protein Shows an Increased Affinity to the Human ACE2 Receptor: An In Silico Analysis

Abstract: The rise of SARS-CoV-2 variants, with changes that could be related to an increased virus pathogenicity, have received the interest of the scientific and medical community. In this study, we evaluated the changes that occurred in the viral spike of the SARS-CoV-2 Omicron variant and whether these changes modulate the interactions with the angiotensin-converting enzyme 2 (ACE2) host receptor. The mutations associated with the Omicron variant were retrieved from the GISAID and covariants.org databases, and a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 44 publications
8
73
0
Order By: Relevance
“…This result for Omicron is qualitatively in agreement with several other theoretical calculations that are appearing in the literature (Ford et al, 2021; Han et al, 2022; Hanai, 2022; Lan et al, 2022; Lupala et al, 2022; Nie et al, 2022, 2022; Ortega et al, 2021). For example, Ortega and colleagues reported the values of − 109.8(3.5) and − 163.8(4.1) for the Haddock score function for the wt and Omicron, respectively (Ortega et al, 2021). Hanai predicted the following order for some variants (in bold cases that appear in the same order with the present calculations are highlighted): Alpha (276.9 kcal mol − 1 ) < Beta (289.2 kcal mol − 1 ) = Gamma (300.1 kcal mol − 1 ) < WT (301.9 kcal mol − 1 ) < Mu (406.8 kcal mol − 1 ) < Kappa (503.5 kcal mol − 1 ) < Delta (538.1 kcal mol − 1 ) < Omicron (749.8 kcal mol − 1 ) using his molecular interaction energy function (Hanai, 2022).…”
Section: Resultssupporting
confidence: 92%
“…This result for Omicron is qualitatively in agreement with several other theoretical calculations that are appearing in the literature (Ford et al, 2021; Han et al, 2022; Hanai, 2022; Lan et al, 2022; Lupala et al, 2022; Nie et al, 2022, 2022; Ortega et al, 2021). For example, Ortega and colleagues reported the values of − 109.8(3.5) and − 163.8(4.1) for the Haddock score function for the wt and Omicron, respectively (Ortega et al, 2021). Hanai predicted the following order for some variants (in bold cases that appear in the same order with the present calculations are highlighted): Alpha (276.9 kcal mol − 1 ) < Beta (289.2 kcal mol − 1 ) = Gamma (300.1 kcal mol − 1 ) < WT (301.9 kcal mol − 1 ) < Mu (406.8 kcal mol − 1 ) < Kappa (503.5 kcal mol − 1 ) < Delta (538.1 kcal mol − 1 ) < Omicron (749.8 kcal mol − 1 ) using his molecular interaction energy function (Hanai, 2022).…”
Section: Resultssupporting
confidence: 92%
“…7 The structural changes induced by these mutations likely confer stability to CoV-2 as it binds to ACE2. This agrees with the study of Ortega et al, 8 where they found that two main residues (479 and 487) have been associated with human ACE2 recognition. They further found a higher number of residues in the CoV-2 capping loops and attributed the more favorable binding affinity of -15.7 Kcal/mol as opposed to -14.1 Kcal/mol for CoV.…”
supporting
confidence: 93%
“…They further found a higher number of residues in the CoV-2 capping loops and attributed the more favorable binding affinity of -15.7 Kcal/mol as opposed to -14.1 Kcal/mol for CoV. 8 Based on our calculations, there is no significant contribution from a single mutant to the binding energies between the SARS and the ACE2. However, these mutations induce sophisticated structural changes that enhance the electrostatic and van der Waals binding energies (Table S1).…”
supporting
confidence: 49%
“…These mutations were observed in the RBD regions in the emerging viruses. Ortega et al found that these mutations can change the virus binding affinity to the ACE2 receptor (164). Mutation allows the virus to escape the immune system (166).…”
Section: K444rmentioning
confidence: 99%